Smart Ethnomath Game: An Ethnomathematics-Based Digital Game for Improving Numeracy in Geometry - Lisnani Lisnani; Toh Tin Lam; Hilma Alia; Suci Mutiya Ningrum (Journal of Emerging Technologies in Ethnomathematics, 2026)
The background of this research is based on the low numeracy skills of students and the lack of contextual, interesting, and integrating local culture learning media in mathematics learning. The research aims to develop smart ethnomath games which is an interactive learning media based on ethnomathematics on geometry materials to improve numeracy of the students.  This research uses the Research and Development (R&D) method with the ADDIE development model which includes the stages of analysis, design, development, implementation, and evaluation. The subjects of the study were fifth grade students in junior high school students consisting of 60 students. The instruments used included expert validation sheets, student response questionnaires, and numeracy tests. The results of the study show that the smart ethnomath game developed meets the valid criteria with an excellent category based on the assessment of material and media experts. In addition, this media is declared practical to be used based on the positive response of students. The effectiveness test showed that the use of Smart Ethnomath Game was able to significantly improve students' numeracy, especially in understanding geometric concepts contextually. Smart Ethnomath Game can be an innovative alternative in mathematics learning that effectively integrates local technology and culture.